A Strain Gauge Technique for the Dynamic Measurement of Ice - Clark, Don B. (ARCTIC, 1960)
Describes a method of applying strain gauges to ice samples, using a coating material for the gauges to provide high gauge: ice impedance. Results of tests with various coatings are reported; Zerok 110, a styrene-butadiene copolymer, exhibited the best properties. Data are presented of measurements on dynamically loaded strain-gauged cylinders of fresh- and salt-water ice; considerable accuracy is claimed in the determination of the Poisson ratio and Young's modulus.